Short- and long-term effects of musculoskeletal health education: evidence from the performing arts students - Adamčák, Štefan; Marko, Michal; Bartík, Pavol; Kľocová Adamčáková, Zora (Frontiers in Sports and Active Living, 2025)
BackgroundPerforming arts students (i.e., musicians), face elevated risks of performance-related musculoskeletal disorders due to prolonged exposure to static postures, repetitive movements, and lack of ergonomic education. While the benefits of musculoskeletal health education are established in sports, its application and long-term effects in performing arts education remain underexplored. This study aimed to evaluate both short- and long-term effects of musculoskeletal health education on dynamic spine function among female music students.MethodsForty-four female music students from the Academy of Arts in Banská Bystrica participated in a non-randomized controlled study. Participants were divided into an experimental group (n = 28), which received 8-week musculoskeletal health education (2x/week/45 min), and a control group (n = 16), which received no intervention. The education included theoretical and practical components focused on postural awareness and dynamic spine function. Spine mobility was assessed using standardized methods common in medical and physical therapy practice at three time points: pre-test, post-test, and follow-up. Statistical analysis was performed using non-parametric Wilcoxon and Mann–Whitney tests, with significance set at p < .05.ResultsThe experimental group showed statistically significant improvements in all dynamic spine function tests post-intervention (e.g., Schober's: from 2.71 ± .81 cm to 5.60 ± .68 cm, p < .05) with partial retention at follow-up (4.03 ± .79 cm). Significant gains were also observed in Thomayer's test (from −7.46 ± 4.66 cm to −.78 ± 1.39 cm), indicating enhanced spine mobility. In contrast, the control group demonstrated significant declines across all parameters over time. Intergroup comparisons post-intervention and at follow-up revealed significantly better outcomes in the experimental group across all measures (p < .05), confirming the effectiveness of education.ConclusionsMusculoskeletal health education program led to significant short- and long-term effects on dynamic spine function in female music students. The results underscore the importance of integrating such programs into performing arts curricula to prevent musculoskeletal decline and promote health literacy. This study provides compelling evidence that musculoskeletal education, when embedded into arts training, is both a preventive and rehabilitative tool essential for sustaining the physical well-being of performing arts students.